Communicating with data visualisation a practical guide - Frost, Adam (Information scientist); Sturt, Tobias; Kynvin, Jim; Fernández Gallardo, Sergio (SAGE, 2022)
How can you transform a spreadsheet of numbers into a clear, compelling story that your audience will want to pass on? This book is a step-by-step guide (honed through the authors' Guardian masterclasses, workshops and seminars) to bringing data to life through visualisations, from static charts and maps to interactive infographics and motion graphics. Introducing a four-step framework to creating engaging and innovative visualisations, it helps you to: Find the human stories in your datasets, Design a visual story that will resonate with your audience, Make a clear, persuasive visual that represents your data truthfully, Refine your work to ensure your visual expresses your story in the best possible way. This book also includes a portfolio of best-practice examples and annotated templates to help you choose the right visual for the right audience, and repurpose your work for different contexts.